The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1136/archdischild-2017-314064
|View full text |Cite
|
Sign up to set email alerts
|

Delivery of positive end-expiratory pressure to preterm lambs using common resuscitation devices

Abstract: PEEP delivery with SIBs depends on the set PEEP, inflation rate, device model and gas flow. At recommended inflation rates of 60/min, some devices can deliver PEEP close to the set level, although the reduction in PEEP makes some SIBs potentially less effective for lung recruitment than a T-piece.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 34 publications
0
3
0
1
Order By: Relevance
“…The TPR is widely used for neonatal resuscitation and resuscitation of infants <10 kg around the world and is recommended as the primary modality to deliver newborn resuscitation. In manikin models, it has been demonstrated that a TPR provides consistent and accurate pressures in neonatal (18). The lung compliance or Rrs of the system was not recorded.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The TPR is widely used for neonatal resuscitation and resuscitation of infants <10 kg around the world and is recommended as the primary modality to deliver newborn resuscitation. In manikin models, it has been demonstrated that a TPR provides consistent and accurate pressures in neonatal (18). The lung compliance or Rrs of the system was not recorded.…”
Section: Discussionmentioning
confidence: 99%
“…Hinder et al studied TPR on a test lung with varying compliance and reported a significant increase in PEEP with increased compliance ( 17 ). Thio et al examined preterm lambs using a TPR and SIB at set PEEP (5, 7, 10 cmH 2 O) with set PIP of 30 cmH 2 O and varying rates at 20, 40 and 60 ipm with and without gas flow ( 18 ). The lung compliance or R rs of the system was not recorded.…”
Section: Discussionmentioning
confidence: 99%
“…Mit einem selbstfüllenden Beatmungsbeutel kann grundsätzlich kein CPAP verabreicht werden und selbst mit einem PEEP-Ventil ist die Verabreichung eines konstanten endexspiratorischen Drucks wahrscheinlich kaum möglich [226][227][228][239][240][241][242]. Die Produkteigenschaften verschiedener T-Stück-Systeme und auch selbstfüllender Beatmungsbeutel variieren erheblich, mit Auswirkungen während ihrer Verwendung [243].…”
Section: Hilfsmittel Zur Assistierten Beatmungunclassified
“…[12][13][14][15][16][17][18] PEEP valves for self-inflating bags (SIBs) exist, but serious concerns have been raised about the ability of these to deliver reliable PEEP. [19][20][21][22] Researchers of 4 randomized controlled trials (RCTs) have investigated PEEP delivered by different devices at birth. [23][24][25][26] Two studies included term in addition to preterm newborns but did not report the effects for term newborns alone.…”
mentioning
confidence: 99%